Anatomical Insights of the Internal Carotid Artery Dural Rings: Endonasal and Transorbital Comparative Perspective - Manfrellotti, Roberto; Mosteiro, Alejandra; Gagliano, Dario; López, Lorena Gómez; Lasunin, Nikolay; Valdivia, Doriam Perera; Giussani, Carlo Giorgio; Carrabba, Giorgio Giovanni; Torné, Ramon; Prats-Galino, Alberto; Somma, Alberto Di; Enseñat, Joaquim (Journal of Neurological Surgery Part B: Skull Base, 2025)
The clinoidal segment of the internal carotid artery (ICA) is a complex transition zone between the intracavernous and intradural spaces. It is bordered by the distal dural ring (DDR), proximal dural ring (PDR), and anterior clinoid process (ACP). This study provides an endoscopic anatomical analysis of the clinoidal region using the endonasal endoscopic approach (EEA) and endoscopic transorbital approach (ETOA).Ten cadaveric head specimens were dissected at the Laboratory of Surgical Neuroanatomy of the University of Barcelona.EEA exposes the medial clinoidal region, revealing the connection between the PDR and parasellar ligaments, although their individual components remain indistinct. ACP removal clarifies the relationship between DDR, the falciform ligament, and the diaphragma sellae. ETOA provides access to the outer clinoidal region, isolating PDR and DDR and detailing their continuity with adjacent ligaments.EEA and ETOA offer comprehensive insights into the clinoidal region's anatomy.
Keywords: carotid region; distal dural ring; endoscopic endonasal approach; endoscopic transorbital approach; proximal dural ring